Students in the Sex Industry: Motivations, Feelings, Risks, and Judgments - Ernst, Felicitas; Romanczuk-Seiferth, Nina; Köhler, Stephan; Amelung, Till; Betzler, Felix (Frontiers in Psychology, 2021)
Student sex work is a current phenomenon all over the world, increasingly reported by the media in recent years. However, student sex work remains under-researched in Germany and is lacking direct first-hand reports from the people involved. Further, sex work remains stigmatized, and therefore, students practicing it could be at risk of social isolation and emotional or physical danger. Therefore, this study examines students working in the sex industry focusing on their personal experiences and attitudes toward them. An online questionnaire was completed by 4386 students from Berlin universities. Students who identified themselves as sex workers (n = 227) were questioned with respect to their motivations to enter the sex industry, characteristics of their job, feelings after the intercourse, and perceived risks. Student non-sex workers (n = 2998) were questioned regarding knowledge of and attitudes toward student sex workers. Most student sex workers reported that they entered the sex industry due to financial reasons (35.7%). The majority reported offering services involving direct sexual intercourse. Disclosing their job to friends, family, or others was associated with less problems with social isolation and in romantic relationships. With a total of 22.9%, student non-sex workers reported never having heard about students working in the sex industry. The most frequent emotions mentioned by them with regard to student sex workers were compassion and dismay (48.9%). There was no difference in happiness between student sex workers and non-sex working students. Through this research, it becomes evident that there are similarities between the student’s motivations to enter the sex industry, their feelings, and the problems they have to face. Moreover, prejudices still prevail about the life of student sex workers. Increasing understanding of student sex work might help those sex workers to live a less stigmatized life and thereby to make use of support from others. The universities as institutions could form the basis for this, e.g., by openly supporting student sex workers. This could help to encourage the rights of student sex workers and to gain perspective with respect to the sex industry.